Corporate Restructuring, Firm Characteristics and Implications on Capital Structure: an Academic View - Marimuthu, Maran (2009)
The fundamental reason for carrying out corporate restructuring is to further enhance the long-term survival of firms through greater efficiency and cost-effectiveness. As a result, firms are bound to conduct financial restructuring as part of their corporate restructuring program. This involves some adjustment on their capital structure as there is a need to have changes on either their debt proportions or equity proportions. This article explores certain critical areas of capital structure. The argument here is based on the life cycle of a company, firm specific characteristics and type of business dimensions. This study also offers a conceptual understanding on capital structure in a given set of factors/variables. It is also postulated here that researchers should look into the possibility of remodeling their work on capital structure.